Upaya Pemanfaatan Limbah Plastik Melalui Pelatihan Pembuatan Sandal Dari Kresek Bekas - Erny Untari; Indra Puji Astuti (Universitas PGRI Adi Buana Surabaya, 2021)
Community service activities carried on 8-11 May 2021, located in Bulu viilage, Sukomoro sub district, Magetan Regency, has made a very significant contribution to the community, especially in Bulu viilage, Sukomoro district, Magetan Regency. Community service activities include how to use garbagr and make slippers from used crackle by Bulu village, Sukomoro district, Magetan Regency. Receipt of material abaout how to make slippers from used crackle is very meaningfull to the people of Bulu village, Sukomoro district Magetan Regency in order to increase family income. Community service activities with the theme “Training On Making Slippers From Used Crackle” which took place in the PKK orphonage building Bulu village, Sukomoro district, Magetan regency was attented by participants all of them 21 mothers, activator of Bulu village, team leader PKK activator of Bulu village, RT 02 RW 03 Bulu village head, 2 lecture, and 2 students.This training is a community servicee program by PGRI Madiun University lectures. This training was carried out in order to help the community, especially mothers of Bulu village residents, Skomoro district Magetan regency to obtain additional income. Seeing anthusiasm of the participants there will be an impact of this training that residents can make slippers from used crackle and eventually can increase family income.